You can't make an omelette without breaking eggs: the impact of venture capitalists on executive turnover - Diana Heger; Tereza Tykvová (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
We present evidence on venture capitalists? (VCs) impact on turnover of executives for a sample of nearly 47,000 German high-tech start-ups between 1995 and 2004. We confirm that the presence of VCs increases the probability of a change in the initial executive team. Additionally, we take a closer look on the subsample of venturebacked firms. We find that a small distance between the VCs and the companies they finance and a larger total stake in the company owned by VCs increase the probability of changes in the initial executive teams.
Keywords: G32; G24; 330; Venture Capital; Executive Turnover